Age-Related Changes in Motor Cortical Representation and Interhemispheric Interactions: A Transcranial Magnetic Stimulation Study - Coppi, Elisabetta; Houdayer, Elise; Chieffo, Raffaella; Spagnolo, Francesca; Inuggi, Alberto; Straffi, Laura; Comi, Giancarlo; Leocani, Letizia (Frontiers in Aging Neuroscience, 2014)
To better understand the physiological mechanisms responsible for the differential motor cortex functioning in aging, we used transcranial magnetic stimulation to investigate interhemispheric interactions and cortical representation of hand muscles in the early phase of physiological aging, correlating these data with participants’ motor abilities. Right-handed healthy subjects were divided into a younger group (n=15, 25.4 ± 1.9 y.o) and an older group (n=16, mean age 61.1 ± 5.1 y.o). Activity of the bilateral abductor pollicis brevis (APB) and abductor digiti minimi (ADM) was recorded. Ipsilateral silent period (ISP) was measured in both APBs. Cortical maps of APB and ADM were measured bilaterally. Mirror movements (MM) were recorded during thumb abductions. Motor abilities were tested using Nine Hole Peg Test (NHPT), finger tapping (FT) and grip strength. ISP was reduced in the older group on both sides, in terms of duration (p=0.025), onset (p=0.029) and area (p=0.008). RMT did not differ between groups. APB and ADM maps were symmetrical in the younger group, but were reduced on the right compared to the left hemisphere in the older group (p=0.008). The APB map of the right hemisphere was reduced in the older group compared to the younger (p=0.021). Older subjects showed higher frequency of MM and worse motor abilities (p<0.001). The reduction of right ISP area correlated significantly with the worsening of motor performances. Our results showed decreased interhemispheric interactions in the early processes of physiological aging and a decreased cortical muscles representation over the non-dominant hemisphere. The decreased ISP and increased frequency of MM suggest a reduction of transcallosal inhibition. These data demonstrate that early processes of normal aging are marked by a dissociation of motor cortices, characterized, at least, by a decline of the non-dominant hemisphere, reinforcing the hypothesis of the right hemi-aging model.